Modification to knowledge on therapeutic adherence in aged women with breast cancer by means of an educational program - Yudmila María Soler Sánchez; Elsa Pérez Rosabal; Martha del Carmen López Sánchez (Centro Provincial de Información de Ciencias Médicas, 2016)
An educational intervention study of 15 aged women with breast cancer, belonging to "Ángel Ortiz Vázquez" Polyclinic from Manzanillo municipality in Granma province was carried out from August to November, 2013, with the aim of modifying their knowledge on therapeutic adherence by means of an educational program.  Among the analyzed variables there were: school level, marital status, knowledge on breast cancer and knowledge on therapeutic adherence.  The information was obtained from the minimum exam of the mental status and from the survey.  The educational program was conformed by 10 sessions, and it allowed the members of the series to elevate their knowledge level on the topic.